Packing Them In Festivals in Athens and Cambridge - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Festivals in Athens and Cambridge. It's time Fin Walker assumed her rightful place in the front rank of British dance-makers. PALABRAS CLAVE: British Dance Edition (BDE), national dance agencies (NDA), Fin Walker, Silence of the Soul.